Dynamic Governance in Countering Terrorism in Indonesia: A Discourse Network Analysis on Online News Media - Amin, Muhammad Ikhsanul; Wahyunengseh, Rutiana Dwi (KnE Social Sciences, 2022)
Countering terrorism involves new challenges amid the increasing use of information technology. This has implications for the emergence of various modes of terrorism that are increasingly disruptive. This research examined the use of dynamic governance in efforts to create dynamic and contextual policies in establishing comprehensive and targeted counter-terrorism programs. Qualitative methods were used with a discourse network analysis approach. The data were collected from online news media sources (Kompas.com and Okezone.com) about content related to countering terrorism between 2018-2020. The results of the study showed that only a few governance actors carried out comprehensive discourse on dynamic governance in countering terrorism. In addition, some of the systematization of the concept caused polemics among the stakeholders involved, so that not all actors were in agreement with the meaning of dynamic governance. This article recommends that, on the one hand, each actor must carry out benchmarking so that they have the same capacity in actualizing the concept of dynamic governance, while on the other hand, the government must pay attention to the participation of each actor in order to ensure a consistent paradigm is used in countering terrorism. Keywords: counter terrorism, discourse network analysis, disruption, dynamic governance, policy contextualization